Listening Metacognitive Awareness: Case Study on Chinese and Russian Students in French L2 (JOURNAL OF ADVANCES IN LINGUISTICS, 2017)
Closely connected with other language skills, listening plays an essential role in language acquisition that is why perception of authentic speech is one of the most important aspects of language teaching and development of learners listening strategies is substantial in language teaching.  In this paper, we examine French and English literature on this topic. We conduct our study by means of a questionnaire among 21 Chinese and 21 Russian university students who achieved at least Intermediate level in French L2. The data analysis allows us to show how difficult listening is for the students and also to demonstrate which metacognitive listening strategies they use. Finally, we draw some trends in L2 listening among interviewed Chinese and Russian students.